KAJIAN LITERATUR SIMULASI PENGARUH PENERAPAN UNDERPASS DI PERSIMPANGAN KENTUNGAN YOGYAKARTA TERHADAP BEBERAPA PERSIMPANGAN LAINNYA - Raharja, Adyk Marga; Dharma, I Gusti Bagus Budi (SENATIK STT Adisutjipto, 2017)
The intersection of Kentungan is one of the intersections that connects North Ringroad Road and Kaliurang Street which looks increasingly stuck in Yogyakarta. This is due to an uneven increase in vehicle vehicles to road infrastructure. The peak of traffic jam at Intersection of Junction often occurs at 16.00-17.30 WIB. The problem at this junction is the amount of time delay and the length of the queue. One way to reduce congestion problems at the Intersection is to construct road infrastructure, one underpass. Based on these problems, research on the effect of underpass application on congestion parameters at several other intersections adjacent to the intersection of Kentungan. This research is a Multi Channel Multi Phase model configuration, by creating an underpass model of the Autodesk Infraworks 360 software. Before modeling underpass conditions, it is done in advance of the existing model of Intersection of Kentungan. The data inputted to this existing model is the total data of vehicles crossing the intersection of Kentungan for one hour. Verification model in this research is done by visual testing and check the duration of green light at the time of simulation done. Validation in this research is done by using hypothesis test, paired t-test. Then the parameters for validation are data ie the average waiting time of the vehicle, the maximum queue length and the number of vehicles passing through the green light in one cycle.In this study using two scenarios, in scenario 1 is the underpass model with the condition of the intersection and the scenario 2 is the underpass model with the roundabout condition. The results obtained from both scenarios are compared with the existing model results. The compared parameters are the average vehicle delay time and maximum queue length on each approach. It is expected from the comparison analysis to show that the Kentungan Intersection after the built underpass has decreased significantly on the average delay time and maximum queue length .